Dual-T-Type Five-Level Cascaded Multilevel Inverter with Double Voltage Boosting Gain - Lee, Sze Sing; Lim, Chee Shen; Siwakoti, Yam P.; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2020)
The switched-capacitor-based cascaded multilevel inverters (CMI) have been emerging due to their voltage boosting capability. Unfortunately, they suffer from impulse charging current and nonuniform operation. This article presents a topology termed as dual-T-type five-level CMI to resolve these problems without compromising the desirable voltage boosting characteristic. The main idea is to integrate a half bridge and an inductor to soft charge a capacitor that is connected in series with the dc source. The capacitor enables the voltage gain boosted to two, while the control of eight power switches that constitutes a dual-T structure enables five voltage levels generation. In addition, uniform operation is achieved for cascaded extensions. The operating principle of the proposed topology is analyzed and elaborated. For validation, simulation, and experimental results of a prototype are presented.
Keywords: Cascaded multi-level inverters; Charging current; Operating principles; Power switches; Switched capacitor; Voltage boosting; Voltage gain; Voltage levels; Cascaded multilevel inverter; Dual-T-type topology; Soft charging; Switched-capacitor; Voltage boosting